PENINGKATAN KEMAMPUAN MENYIMAK MELALUI METODE MENDONGENG MENGGUNAKAN MEDIA PAPAN FLANEL ANAK USIA 5-6 TAHUN - Krisensiana, Krisensiana; R, Marmawi; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractAs a technique in learning, fairy tales are beneficial for children in developing cognitive, affective, and psychomotor aspects. Because through stories, children get information about facts, concepts, as well as knowledge that is connected in a story. From the initial observations made by the author, it was shown that as many as 24 children there were 6 BB children, 12 MB children, 4 BSH children, and 2 BSB children. Indicators of listening skills appear, such as listening attentively, interpreting stories and understanding meaning. As also stated by the Head of Kindergarten and some teaching teachers, that the low listening skills of students can be seen from the communication they use everyday in school, sometimes there are also children who do not want to answer if there are questions from the teacher or in other activities. In addition, the storytelling method has not been used in accordance with the application of storytelling methods in an effort to improve listening skills in children. Keywords: story telling, fairy tales